Bi-heterociclos a partir do Ácido Levulínico: Síntese de 5-[(5-(trifluormetil)-5-hidroxi-(3-substituido)-4,5-diidro-1H-pirazol-1-il)-1-propan-1-ona-3-il]-2-metil-7-trifluormetil)pirazolo[1,5-a]pirimidinas - Rosales, Pauline Fagundes (2013)
An efficient method to obtain 2-methyl-5-(methylpropanoate-3-yl)-7-trifluoromethylpyrazolo[1,5-a]pyrimidine 2 from the reaction of compound methyl 7,7,7-trifluoro-4-methoxy-6-oxo-heptenoate with 3-amino-5-methyl-1H-pyrazol. This compound 2 brought to reaction with hydrazine monohydrate to obtain 2-methyl-7-trifluoromethylpyrazolo[1,5-a]pyrimidine-5-propanehydrazine 3 and after were later brought to cyclocondensation reaction with a series of β-alkoxyvinyltrifluoromethyl ketones giving the series of news bi-heterocyclic 5-[(5-(trifluoromethyl)-5-hydroxy- (3-substituted)-4,5-dihydro-1H-pyrazol-1-yl)-1-propan-1-one-3-yl]-2-methyl-7-trifluoro methyl)pyrazolo[1,5-a]pyrimidines compounds 5a-l. Compound 2-methyl-5-(methylpropanoate-3-yl)-7-trifluoromethylpyrazolo[1,5-a]pyrimidine 2 brought to transesterification reaction and hydrolises reaction for obtaining the compounds 6 and 7. The structures of all synthesized compounds were confirmed by 1H, 13C, 19F NMR data, and two-dimensional NMR techniques like HETCOR and COLOC, mass spectrometry data.